Multicultural Counseling Practices in Junior High Schools: A Systematic Literature Review - Lidia Jelaus; Amelia Juloma Mboes; Priska Diana Lisa (CERDAS AKADEMIKA NUSANTARA, 2026)
The growing cultural diversity in school environments demands guidance and counseling services capable of accommodating students’ diverse backgrounds. This study aims to examine the implementation of multicultural counseling at the junior high school (SMP) level using the Systematic Literature Review (SLR) method. The article search was conducted using the Google Scholar database with the keywords multicultural counseling, multicultural guidance and counseling, and Junior High School (SMP). The articles reviewed were scientific publications released between 2020 and 2026. Of the 7 articles obtained during the identification stage, 4 met the inclusion criteria and were used in the review process. The data were analyzed through the stages of identification, selection, evaluation, and synthesis of research findings to obtain an overview of the implementation of multicultural counseling in junior high schools. The study findings indicate a positive trend in the implementation of multicultural counseling to support student development. This service shows positive impacts on improving cross-cultural communication, fostering empathy and tolerance, reducing social prejudice, enhancing emotional regulation skills, and promoting acceptance of cultural diversity within the school environment. Additionally, the creativity of guidance and counseling teachers in managing these services contributes to the effectiveness of multicultural counseling implementation. These findings suggest that multicultural counseling has the potential to be a relevant approach in fostering an inclusive, harmonious, and diversity-respecting school environment.